Radiological Significance of Shear-Wave Elastography Technique for Evaluation of Solid Breast Masses with Histopathological Correlation - Sahu, Niranjan; Agrahari, Ashish Kumar; Parida, Bikash; Das, Somadatta (AL-Kindy College Medical Journal, 2023)
Background: Although various imaging modalities are available for evaluating suspicious breast lesions, ultrasound-based Shear-Wave Elastography (SWE) is an advanced, non-invasive technique complementary to grayscale sonography. This technique evaluates the elasticity of a specific tissue by applying sonic pressure to that tissue.Objective: The aim is to assess the role of SWE in evaluating solid breast masses in correlation to histopathological study results.Subjects and Methods: This prospective study was done in a tertiary care teaching hospital from September 2019 to August 2020. A study population of 50 women aged 18 years or above with an ultrasonographic (USG) diagnosis of solid breast masses was included.Results: A significantly higher value of SWE elasticity ratio (E-mean) was observed in malignant tumors than in benign tumors (p